High-energy diet enhances spermatogenic function and increases sperm midpiece length in fallow deer (Dama dama) yearlings - Ros-Santaella, José Luis (R Soc Open Sci, 2019)
Nutrition is a major factor involved in the sexual development of livestock ruminants. In the male, a high-energy diet enhances the reproductive function, but its effects on the underlying processes such as spermatogenic efficiency are not yet defined. Moreover, the possible changes in sperm size due to a supplemented diet remain poorly investigated. The main goal of this study was to evaluate whether a high-energy diet affects the spermatogenic activity, epididymal sperm parameters (concentration, morphology, morphometry and acrosome integrity) and blood testosterone levels in fallow deer yearlings. For this purpose, 32 fallow deer were allocated into two groups according to their diet: control (pasture) and experimental (pasture and barley grain) groups. Fallow deer from the experimental group showed a significant increase in the Sertoli cell function and sperm midpiece length, together with a higher testicular mass, sperm concentration and percentage of normal spermatozoa than the control group (p < 0.05). We also found a tendency for higher blood testosterone levels in the animals fed with barley grain (p = 0.116). The better sperm quality found in the experimental group may be related to their higher efficiency of Sertoli cells and to an earlier onset of puberty. The results of the present work elucidate the mechanisms by which dietary supplementation enhances the male sexual development and might be useful for better practices of livestock management in seasonal breeders.